Modernization of the education system within the context of Russia’ accession to world trade organization - O. I. Seliverstova (Высшее образование в России)
The article is devoted to the assessment of the influence of Russia’s entry to WTO on the sphere of educational services. The author analyzes the specific commitments of the Russian Federation related to incurrence on the General Agreement on Trade in Services during the reform of education legislation. In particular, the rules of the Federal Law «On Education inthe Russian Federation», concerning the educational services, within the context of Russia’sinternational obligations are considered.